Analisis Kemampuan Numerasi Siswa SMP Dalam Memecahkan Masalah Kontekstual Matematika - Putra, Aditya Rizky; Kamid; Gustiningsi, Tria (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study is motivated by the diverse levels of students’ numeracy skills, the underlying factors of which remain unclear based on numeracy indicators. The purpose of this research is to describe junior high school students’ numeracy abilities in solving contextual mathematical problems. A qualitative descriptive method was employed, with the study conducted at SMP Negeri 7 Muaro Jambi. The research subjects were Grade VIII students who participated in the 2024 AKM assessment and had studied the topic of relations and functions, categorized by high, medium, and low mathematics achievement. Data were collected through numeracy tests, interviews, and documentation. The findings reveal that students with high and medium mathematics achievement generally demonstrated high numeracy skills. Meanwhile, those with low academic performance in mathematics exhibited moderate numeracy abilities. However, mathematics achievement did not consistently reflect students’ actual numeracy levels. This was evidenced by cases where a high-achieving student displayed only moderate numeracy, while some medium and low achievers showed high numeracy proficiency. Penelitian ini dilatarbelakangi oleh beragamnya kemampuan numerasi siswa yang belum diketahui faktornya berdasarkan indikator kemampuan numerasi. Penelitian ini bertujuan untuk mendeskripsikan kemampuan numerasi siswa SMP dalam memecahkan masalah kontekstual matematika. Metode penelitian yang digunakan adalah deskriptif kualitatif. Tempat penelitian ini adalah SMP Negeri 7 Muaro Jambi. Subjek dalam penelitian ini adalah siswa kelas VIII yang mengikuti tes AKM tahun 2024 dan telah belajar materi relasi dan fungsi dengan nilai hasil belajar matematika tinggi, sedang dan rendah. Alat pengumpul data yang digunakan dalam penelitian ini yaitu lembar tes kemampuan numerasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa siswa dengan nilai hasil belajar matematika tinggi dan sedang memiliki tingkat kemampuan numerasi yang tinggi. Siswa dengan nilai hasil belajar matematika rendah memiliki kemampuan numerasi yang sedang. Hasil belajar matematika siswa tidak menunjukkan tingkat kemampuan numerasi siswa, terbukti dari adanya salah satu siswa bernilai tinggi dengan kemampuan numerasi sedang, serta salah satu siswa bernilai sedang dan rendah dengan kemampuan numerasi tinggi